Stability of salivary microRNA measures across an NCAA Division I football season: Implications for microRNA as a biomarker of concussion - Thomas R. Campbell; Martina Zamponi; Delaney Leathers; Julie Cavallario; Jessica C. Martinez; Peter A. Mollica (PLoS ONE, 2026)
Background Clinicians often face challenges in concussion care due to a heavy reliance on subjective patient input. Recently, research has sought objective biomarkers, like salivary microRNAs, to improve concussion management. However, significant limitations hinder the use of microRNAs as a diagnostic tool, including the cumulative effects of a contact sport season. A better understanding of the response to a contact sport season would help researchers and clinicians interpret expression changes at the time of injury in the context of seasonal variation. in Therefore, this study investigated the reliability of previously identified salivary microRNA targets across one contact sport season. Methods This longitudinal study involved 50 male NCAA Division I football players (21 ± 1.6 years; 187.5 ± 6.9 cm; 103.1 ± 19.8 kg). Saliva was collected before the season’s first contact practice and within 72 hours of the season’s final game. Quantitative polymerase chain reaction (qPCR) experiments were conducted using pre-selected microRNA targets. Non-parametric tests compared expressions between time points (α ≤ 0.05). Results No significant differences were found between pre- and post-season miRNA ( p = .07−.46). However, intraclass correlation coefficients revealed low to moderate reliability across the season (ICC = −.04−.65). Conclusions Our study found no significant differences in time points for target microRNA, but ICC statistics indicated low reliability across the season. These findings suggest that microRNA expression may be variable throughout the season regardless of concussive trauma, and clinicians should be aware that changes in microRNA expression should not be directly attributed to concussive forces. Researchers and clinicians should not rely on the presented set of microRNA to make clinical decisions for potential concussive injuries.